Typical Course of Atypical Pneumonia in Children - Ye.I. Yulish; O.Ye. Chernyshova; A.A. Konyushevskaya; S.Ya. Yaroshenko; V.S. Kolesnikova (Zaslavsky O.Yu., 2014)
The article deals with atypical pneumonias caused by Mycoplasma pneumoniae, the features of their clinical picture, diagnosis and treatment. The article presents the cases of clinical observation of children with mycoplasmal pneumonia.